Influência de espaçamentos e consórcios na qualidade bromatológica de silagem de milho - Ferreira, João Paulo [UNESP]; Andreotti, Marcelo [UNESP]; Pascoaloto, Isabô Melina [UNESP]; Costa, Nídia Raquel [UNESP]; Augusto, Jeferson Garcia [UNESP] (My University, 2017)
Attending to the quality of the food provided to the animals is as important as for their quantity. The aim was to analyze corn silages produced in different spacing and consortia. The treatments were corn harvest for silage at spacings of 0.45 and 0.90 m and in consortium with xaraés grass or tanzania grass. The productivity and the bromatological quality of the silage and the material before being silage were evaluated. Maize with tanzania grass at 0.90 m resulted in higher productivity and digestibility.
Influence of spacing and consortia in bromatological quality of maize
Keywords: Integrated Crop-Livestock; Megathyrsus maximum; Urochloa brizantha